2020
DOI: 10.21203/rs.3.rs-23615/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Luteolin Inhibits Respiratory Syncytial Virus Replication by Regulating the MiR-155/SOCS1/STAT1 Signaling Pathway

Abstract: Background Respiratory syncytial virus (RSV) is a major cause of acute lower respiratory tract infection in infants, children, immunocompromised adults, and elderly individuals. Currently, there are few therapeutic options available to prevent RSV infection. The present study aimed to investigate the effects of luteolin on RSV replication and the related mechanisms. Material and methods We pretreated cells and mice with luteolin before infection with RSV, the virus titer, expressions of interferon (IFN)-stim… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Luteolin is a typical flavonoid compound and has been widely studied for its effects, including antioxidant, anticancer, anti-inflammatory, and antiapoptotic [19]. Wang et al found that luteolin can decrease the titer of RSV and inhibit viral replication [20]. Kaempferol, known as polyphenol, was a flavonol present in different plants.…”
Section: Biomed Research Internationalmentioning
confidence: 99%
“…Luteolin is a typical flavonoid compound and has been widely studied for its effects, including antioxidant, anticancer, anti-inflammatory, and antiapoptotic [19]. Wang et al found that luteolin can decrease the titer of RSV and inhibit viral replication [20]. Kaempferol, known as polyphenol, was a flavonol present in different plants.…”
Section: Biomed Research Internationalmentioning
confidence: 99%